Emergent academic English as a lingua franca in the UAE: in-depth analysis of the ZAEBUC-50 corpus - Parra-Guinaldo, Víctor (Frontiers in Communication, 2026)
Comprehensive morpho-syntactic analyses in the description of English as a lingua franca (ELF) are to date not very common, especially in the Gulf region, and the present paper attempts to remedy this lacuna. Following Parra-Guinaldo and Lanteigne’s (2020) study of morpho-syntactic features of transactional ELF and their classification of linguistic variants into processes and categories, this study provides a qualitative analysis of the morphology and syntax of a selection of 50 writing samples produced by first-year students of English contained in the recently compiled Zayed Arabic-English Bilingual Undergraduate Corpus (ZAEBUC) (Habash and Palfreyman, 2022). The study examines grammatical features by integrating insights from generative grammar and usage-based linguistics and situates them within the context of previous lexico-grammar studies. Based on novel uses of the language identified in the data, the paper posits the emergence of a new variety of ELF within the Gulf region (Gulf English) in that some of the linguistic variants found in the study seem a priori particular to this region. Important observations include the sui generis use of generic forms, morphological reanalysis, anticipatory 3rd person singular -s, phantom pronouns, and intruding constituents. Not only have these processes been identified and classified within the corpus, but plausible motivations behind these have also been hypothesized.